Analisis kemampuan peserta didik dalam memecahkan masalah soal cerita pada materi volume bangun ruang ditinjau dari gaya kognitif - Mifta Nurjannah; Hasan Mahfud; Supianto Supianto (Universitas Sebelas Maret, 2024)
This study aims to describe the problem solving ability of story problems with volume material based on the cognitive style of each student. This research uses a qualitative approach with descriptive methods. Sampling using purposive sampling technique on students of class V B SDN Cengklik. Data collection was done using tests, interviews, and documentation studies. The data validity test technique used was triangulation technique. Data analysis used the Miles and Huberman model technique. Based on the results of research and discussion, the score of problem solving ability in students with cognitive style field independent class V B SDN Cengklik is 98, while students with cognitive style field dependent have an average score of 54 problem solving ability. Score problem solving ability in cognitive style group field independent analyzed based on each indicator is 92, meanwhile field independent’s is 25. It shows that the problem solving ability on cognitive style field independent classified as very good, while problem solving ability in cognitive style field dependent classified as very less. Theoretically, the implications of this research enrich the understanding of problem solving ability across cognitive styles. Practically, this research helps educators in adjusting mathematics learning for each student.